Future developments in IMC: why e-mail with video trumps text-only e-mails for brands. (10th April 2017) - Scheinbaum, Angeline Close; Hampel, Stefan; Kang, Mihuyn
Abstract : Purpose: Marketers use e-mail in new, potentially more informative, entertaining and lucrative ways – such as embedding video. The purpose of this paper is to examine consumer responses to audiovisual (i.e. text along with a short video) versus text-only messages in brand communication. Specifically, authors seek to uncover the efficacy of marketer-embedded video (vs text-only) in e-mail on the consumer's product interest, informativeness, perceived prestige, electronic word-of-mouth (e-WOM) intentions and willingness to pass the electronic message along digitally or on social media. With the dual coding theory and selective visual attention as theoretical guideposts, the intended contribution is a framework that can explain and predict advantages for multi-modal e-mail marketing communications. Design/methodology/approach: Five hypotheses are tested experimentally with a one-factor experiment with two conditions (text-only vs audiovisual). The sample was 240 adult participants. Real brands (Audi and Apple) were used. For both brands, participants were randomly assigned to one of two conditions of the e-mail (i.e. audiovisual vs text-only). The stimuli are identical, with the exception of embedded video in the e-mail body. The videos are authentic brand videos, are approximately 50 s and use a product feature appeal. Participants' pre-existing brand attitude was measured. Then, five dependent variables (product interest, informativeness, perceived prestige, e-WOM intentions and willingness to pass the electronic message along digitally or on social media) were considered with respect to consumer exposure to e-mail with video and text in the e-mail from the brand versus text-only e-mail from the brand. Findings: The results supported the hypotheses that audiovisual messages (i.e. those with text and video) heighten informativeness, product interest, perceived prestige, intentions to spread e-WOM for a brand and willingness to pass along the e-mail along to friends and family when compared to text-only messages. These experimental findings from a one-factor experiment with two conditions (text-only vs audiovisual) are generally consistent for an American consumer technology brand Apple (iPhone) and a German luxury automobile brand Audi (S4). Hypotheses are supported for both brands (Apple and Audi), with the exception of product interest for Audi, which may be explained by the high price of a luxury automobile. Research limitations/implications: An implication here for the dual coding theory is that the theory may be extended to consider what happens after the consumer codes the information with both the verbal and the non-verbal subsystem. The finding of interest to information processing scholars is that a video accompanying text communication from a brand to a consumer has an advantage over text-only communication. Brands that communicate with multi-modal marketing communication have better outcomes in informativeness, brand prestige perceptions and intentions of online consumer behaviors, including positive e-WOM for the brand in general and willingness to pass the specific content along in digital and social media platforms. Consumers can become brand advocates by being more inclined to forward the e-mails with the product short video as well as the e-mail text. Practical implications: Brand marketers should consider e-mail in an integrated brand promotion (IBP) campaign as a cost advantage; one of the reasons e-mail should have a solid place in the IBP toolkit is due to e-mail's relatively low cost. The main cost comes with administration and production of the video. As a managerial implication for advertisers, embedding ads of a short video format in e-mails is a way to be more effective than plain-text e-mails. Short videos in e-mails are a reasonable idea to include in an integrated marketing communications effort (plausibly due to information processing with both a verbal and a non-verbal system). Brands can use videos in e-mails to enhance informativeness regarding products to enhance product differentiation from competitors. Yet, it is important to raise caution with some concerning disadvantages potentially associated with e-mail marketing and video. The three areas of caution include potential issues of privacy, clutter and technical inhibitors. Originality/value: Despite the fact that e-mail is one of the most heavily used communication tools in marketing, there is scarce literature on e-mail and branding. By brands evoking a degree of prestige with embedded videos, consumer willingness to become part of the marketing communications is enhanced, as their e-WOM and willingness to share the branded content increase.